1976
DOI: 10.1039/c39760000497
|View full text |Cite
|
Sign up to set email alerts
|

New pterocarpinoid phytoalexins of soybean

Abstract: Structures have been assigned to two new anti-thora megasperma Drechs. var. sojae or on treatment with fungal pterocarpinoids identified in cupric chloride-cupric ch1oride.l One phytoalexin has recently been treated and pathogen-infected soybean plants.assigned the revised structure (1).2 We report the absolute configuration of this compound and the structures of two isomeric pterocarpinoid phytoalexins, produced in similar quantities by soybeans (var. Amsoy 71).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…These data confirm our earlier results demonstrating that prenylation can occur at both C-2 and C-4 in soybean leading to formation of the three glyceollin isomers (3-5) [2]. Also it is demonstrated that the prenylation occurs after formation of the ptesocarpan moiety.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…These data confirm our earlier results demonstrating that prenylation can occur at both C-2 and C-4 in soybean leading to formation of the three glyceollin isomers (3-5) [2]. Also it is demonstrated that the prenylation occurs after formation of the ptesocarpan moiety.…”
Section: Resultssupporting
confidence: 80%
“…The 360 MHz 'H NMR spectrum of the prenylated product showed aromatic signals at 6 6.25 (d, J = 2 Hz), 6.42 (q, J = 8.2 Hz) and 7.20 (d, J = S), coincident with those assigned to Hre, Ha and H, of 5 [2] and 1 [3]. Together with singlets at 6 6.34 and 7.16, assigned to H4 and Hr, this strongly suggests that the prenyl group is at C-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long retention times of these peaks suggested that they are hydrophobic and might represent the phytoalexin glyceollin (Parniske et al, 1991). Although an authentic mixture of glyceollin isomers (Kape et al, 1992) eluted as two peaks with retention times between 25.6 and 27.4 min, the UVabsorption spectra of the unknowns (data not shown) did not match those of known glyceollin isomers (Lyne et al, 1976;Parniske et al, 1991).…”
Section: Flavonoids In Root Exudates Of Cultivar-specific and -Nonspementioning
confidence: 87%
“…1) (12). Lyne et al (42) have characterized two additional soybean phytoalexins which are structural isomers of glyceollin and which appear to have similar antibiotic characteristics. In this manuscript, glyceollin will be a generic term referring to the glyceollin isomers which co-chromatograph on thin-layer chromatography plates.…”
mentioning
confidence: 99%